Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Clover in vineyards, a potential trap plant for the mealybug Pseudococcus calceolariae—a vector of GLRaV-3 to grapevines but not clover species - Rebecca Gough; Kar Mun Chooi; Manoharie Sandanayaka; Vicky Davis; Duncan Hedderley; Tara Taylor; Daniel Cohen; Cecilia A. Prator; Rodrigo P. P. Almeida; Vaughn A. Bell; Robin M. MacDiarmid (Journal of Pest Science, 2025)
Grapevine leafroll disease (GLD) affects grapevines worldwide. The primary causal agent of GLD is grapevine leafroll-associated virus 3 (GLRaV-3), which spreads to uninfected grapevines via mealybugs and soft-scale insects. Pseudococcus calceolariae (Hemiptera: Pseudococcidae) is a mealybug vector of GLRaV-3 in New Zealand. P. calceolariae also colonizes clovers ( Trifolium spp.) growing naturally as vineyard ground cover. Separating mealybug from GLRaV-3 grapevine host could be enhanced by a trap plant: an alternative host attractive to and retentive of the target pest. We evaluated the association between P. calceolariae and ‘Grasslands Huia’ white clover (GHWC). GHWC seed was sown under grapevines in a commercial vineyard (14 × 0.4 ha plots); the control was under-vine herbicide use (7 × 0.4 ha plots, where only few Trifolium spp. plants grew). After 2 years, GHWC cover peaked at 40% mealybug infestation in 2019. From 2018 to 2021, P. calceolariae detection and abundance on GHWC was significantly higher than plants from the control plots. There was no treatment effect for mealybug infestation of grapevine leaves nor of GLRaV-3 incidence, independent of vintage. A glasshouse trial found no transmission of GLRaV-3 by P. calceolariae to any of 256 plants among five clover cultivars tested ( Trifolium spp.), including GHWC; mealybug transmitted GLRaV-3 to 35 of 107 Nicotiana benthamiana plants. The results showed that in the 5-year period, added GHWC did not decouple P. calceolariae from the grapevine to reduce GLRaV-3 incidence, but rapid colonization of GHWC by mealybug and the lack of GLRaV-3 transmission to GHWC are encouraging. Further evaluation is needed to assess whether plant biodiversity can benefit a GLRaV-3 ecological management objective.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Global drivers of avian haemosporidian infections vary across zoogeographical regions - Alan Fecchio; Nicholas J. Clark; Jeffrey A. Bell; Heather R. Skeen; Holly L. Lutz; Gabriel M. De La Torre; Jefferson A. Vaughan; Vasyl V. Tkach; Fabio Schunck; Francisco C. Ferreira; Érika M. Braga; Camile Lugarini; et al. (Global Ecology and Biogeography, 2021)
Aim Macroecological analyses provide valuable insights into factors that influence how parasites are distributed across space and among hosts. Amid large uncertainties that arise when generalizing from local and regional findings, hierarchical approaches applied to global datasets are required to determine whether drivers of parasite infection patterns vary across scales. We assessed global patterns of haemosporidian infections across a broad diversity of avian host clades and zoogeographical realms to depict hotspots of prevalence and to identify possible underlying drivers. Location Global. Time period 1994–2019. Major taxa studied Avian haemosporidian parasites (genera Plasmodium , Haemoproteus , Leucocytozoon and Parahaemoproteus ). Methods We amalgamated infection data from 53,669 individual birds representing 2,445 species world‐wide. Spatio‐phylogenetic hierarchical Bayesian models were built to disentangle potential landscape, climatic and biotic drivers of infection probability while accounting for spatial context and avian host phylogenetic relationships. Results Idiosyncratic responses of the three most common haemosporidian genera to climate, habitat, host relatedness and host ecological traits indicated marked variation in host infection rates from local to global scales. Notably, host ecological drivers, such as migration distance for Plasmodium and Parahaemoproteus , exhibited predominantly varying or even opposite effects on infection rates across regions, whereas climatic effects on infection rates were more consistent across realms. Moreover, infections in some low‐prevalence realms were disproportionately concentrated in a few local hotspots, suggesting that regional‐scale variation in habitat and microclimate might influence transmission, in addition to global drivers. Main conclusions Our hierarchical global analysis supports regional‐scale findings showing the synergistic effects of landscape, climate and host ecological traits on parasite transmission for a cosmopolitan and diverse group of avian parasites. Our results underscore the need to account for such interactions, in addition to possible variation in drivers across regions, to produce the robust inference required to predict changes in infection risk under future scenarios.

Using biophysical modelling and population genetics for conservation and management of an exploited species, Pecten maximus L. - Natalie Hold; Peter Robins; Claire L. Szostek; Gwladys Lambert; Harriet Lincoln; Lewis Le Vay; Ewen Bell; Michel J. Kaiser (Fisheries Oceanography, 2021)
Connectivity between populations is important when considering conservation or the management of exploitation of vulnerable species. We investigated how populations of a broadcast‐spawning marine species (scallop, Pecten maximus ) that occur in discrete geographic locations were connected to each other. Population genetic insights were related to the outputs from a three‐dimensional hydrodynamic model implemented with scallop larval behaviour to understand the extent to which these areas were linked by oceanographic processes and how this was altered by season and two contrasting years that had strongly different average temperature records (warm vs cold) to provide contrasting oceanographic conditions. Our results span from regional to shelf scale. Connectivity was high at a regional level (e.g. northern Irish Sea), but lower at scales >100 km between sites. Some localities were possibly isolated thus dependent on self‐recruitment to sustain local populations. Seasonal timing of spawning and inter‐annual fluctuations in seawater temperature influenced connectivity patterns, and hence will affect spatial recruitment. Summer rather than spring spawning increased connectivity among some populations, due to the seasonal strengthening of temperature‐driven currents. Furthermore, the warm year resulted in higher levels of modelled connectivity than the cold year. The combination of genetic and oceanographic approaches provided valuable insights into the structure and connectivity at a continental shelf scale. This insight provides a powerful basis for defining conservation management units and the appropriate scale for spatial management. Temporal fluctuations in temperature impact upon variability in connectivity, suggesting that future work should account for ocean warming when investigating population resilience.

High indirect fitness benefits for helpers across the nesting cycle in the tropical paper wasp Polistes canadensis - Robin J. Southon; Emily F. Bell; Peter Graystock; Christopher D. R. Wyatt; Andrew N. Radford; Seirian Sumner (Molecular Ecology, 2019)
Explaining the evolution of helping behaviour in the eusocial insects where nonreproductive (“worker”) individuals help raise the offspring of other individuals (“queens”) remains one of the most perplexing phenomena in the natural world. Polistes paper wasps are popular study models, as workers retain the ability to reproduce: such totipotency is likely representative of the early stages of social evolution. Polistes is thought to have originated in the tropics, where seasonal constraints on reproductive options are weak and social groups are effectively perennial. Yet, most Polistes research has focused on nontropical species, where seasonality causes family groups to disperse; cofoundresses forming new nests the following spring are often unrelated, leading to the suggestion that direct fitness through nest inheritance is key in the evolution of helping behaviour. Here, we present the first comprehensive genetic study of social structure across the perennial nesting cycle of a tropical Polistes — Polistes canadensis . Using both microsatellites and newly developed single nucleotide polymorphism markers, we show that adult cofoundresses are highly related and that brood production is monopolized by a single female across the nesting cycle. Nonreproductive cofoundresses in tropical Polistes therefore have the potential to gain high indirect fitness benefits as helpers from the outset of group formation, and these benefits persist through the nesting cycle. Direct fitness may have been less important in the origin of Polistes sociality than previously suggested. These findings stress the importance of studying a range of species with diverse life history and ecologies when considering the evolution of reproductive strategies.

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

A Palaeoproterozoic multi-stage hydrothermal alteration system at Nalunaq gold deposit, South Greenland - Robin-Marie Bell; Jochen Kolb; Tod Earle Waight; Leon Bagas; Tonny B. Thomsen (Mineralium Deposita, 2017)

Interactive effects of methylphenidate and alcohol on discrimination, conditioned place preference and motor coordination in C57BL/6J mice - William C. Griffin; Robin W. McGovern; Guinevere H. Bell; Patrick K. Randall; Lawrence D. Middaugh; Kennerly S. Patrick (Psychopharmacology, 2013)

The relationship between knowledge of family history and cancer characteristics at diagnosis in women newly-diagnosed with invasive breast cancer - Marijana Lijovic; Susan R. Davis; Pam Fradkin; Jo Bradbury; Maria La China; Max Schwarz; Rory Wolfe; Helen Farrugia; Robin J. Bell (Familial Cancer, 2009)

An Experiment in Institutional Transformation: The NSF ADVANCE Program for Women at the Earth Institute at Columbia University - Robin Bell; Jennifer Laird; Stephanie Pfirman; John Mutter; Roberta Balstad; Mark Cane (Oceanography, 2005)

Boron efficiency in oilseed rape: I. Genotypic variation demonstrated in field and pot grown Brassica napus L. and Brassica juncea L. - James C. R. Stangoulis; Harsharn S. Grewal; Richard W. Bell; Robin D. Graham (Plant and Soil, 2000)

Differential response of oilseed rape (Brassica napus L.) cultivars to low boron supply - Jianming Xue; Minshu Lin; Richard W. Bell; Robin D. Graham; Xiaoe Yang; Yuai Yang (Plant and Soil, 1998)